Система мотивации и стимулирования труда персонала на предприятии - Погорелова, Татьяна Алексеевна; Пузач, Е. К.; Кутик, Ю. С. (НТУ "ХПИ", 2015)
В данной статье раскрыта основная суть мотивации и стимулирования труда персонала, рассмотрено их различие и эффективность для предприятия. В работе наглядно изображено действие стимула и мотива на человека, рассмотрен процесс подготовки мотивационной системы персонала в виде системы. Также проанализированы внутренние и внешние факторы мотива и распространенные методы мотивации персонала.

Motivation and stimulation of the personnel is an important component of successful operation of the enterprise. One of the main problems of enterprises of different ownership forms - is finding effective ways to manage labor to ensure the activation of the human factor. The decisive factor in the causal impact of human activity in the enterprise is their motivation. Staff motivation system - a systemof methods and means, which includes everything that the employee can appreciate and desire and that the employer sostoyanii.Eta article reveals the basic essence of motivation and incentives for staff, discussed their difference and efficiency for predpriyatiya.Rabota clearly shows the effect of the stimulus and motive to person through the process of learning motivation system n ersonala system. Also analyzed the internal and external factors, the motive of awareness and ignorance of the man himself.
The system of motivation and stimulation of the personnel in the enterprise
Keywords: мотивы; факторы мотива; стимулы; методы мотивации персонала; motivation; stimulation; motive factors; incentives; staff efficiency